Predictors of media engagement: factors impacting materials scientists’ intentions to communicate science - Voicu, Dumitrita D. (Frontiers in Communication, 2025)
This study examines the views on the public engagement of materials scientists in Germany and the determinants of their media interactions. It uses data from an online survey designed on the theory of planned behaviour (TPB). Results suggest that the scientists’ willingness to interact with the media is remarkably low. Key TPB components—the scientists’ attitudes, their perceived own skills and the opinions of relevant peers—are significant predictors across different models, with the latter showing the highest significance. Among the additional factors, reducing the workload surprisingly is less important to scientists than the institutional acknowledgment of science communication within their organisations. Younger scientists show the lowest degree of willingness to engage in communication activities and this group is about equally split between those intending to increase or decrease their communication efforts in the future. Thus, organisations aiming to foster their scientists’ commitment to communication should adopt flexible and tailored strategies to suit the needs and priorities of their respective target groups.